(untitled) (Experimental biology, 2016)
The paper discusses the results of a patented preparation isolated from immature seeds of Chinese elm (Ulmusparvifolia) to increase stress tolerance and productivity of cereals. Soaking the seeds of wheat in the microfertilizer solution at a concentration of 60 mg/L prior to planting, resulting in the preservation of high plant productivity in the arid conditions of the south Kazakhstan. The determining factor in the stabilization of growth processes under the influence of the microfertilizer amid the stressful conditions, is the consistent increase in activity of the enzyme complex MDH-GOGAT. At the same moisture of grain tested samples differenced slightly by starch and fiber content and amylase activity of the flour. On the contrary, some indicators characterizing the biological and technological value of the product (protein, gluten and its quality) significantly decreased.But the main indicators of plant productivity (crop, dt per ha), including elements of yield structure (mass of 1000 grains, productive tillering) as well as the rate of photosynthesis in the plant organs in terms of chlorophyll a and b, was significantly higher in the experimental samples.As a result, grain yield on the cultivated area was as follows: in the control variant 12.5 t/ha, and in the experimental plot - 17.8 t/ha. When studying the quantitative quality of mature grain in the same experiments, we found no signs of improvement in the quality of the experimental variants.